P040 Is Vedolizumab the Answer to Decreasing the Incidence of Immune-Mediated Colitis in Patients With Pre-Existing Inflammatory Bowel Disease?. (December 2019) - Jayoushe, Majdoline; Gupta, Nancy; Bellaguarda, Emanuelle
Abstract : INTRODUCTION: Immune checkpoints are immunosuppressive proteins expressed by activated T-lymphocytes which evade the attack of the endogenous immune system on tumor cells. The role of immune checkpoint inhibitors (ICIs) in modern cancer treatment has gained more widespread attention in the last ten years with their favorable outcomes on survival rates. Immune mediated gastrointestinal side effects, including diarrhea and colitis, were reported in approximately 30% of patients receiving therapy with ICIs. Current practice guidelines recommend corticosteroid therapy as first-line management of immune-mediated colitis (IMC), and immunosuppressive therapy, such as with Infliximab or Vedolizumab, for steroid-refractory IMC. Yet, there is very little awareness in the literature on tailoring the management of pre-existing inflammatory bowel disease (IBD) in patients who experience IMC due to ICI therapy. CASE DESCRIPTION: A 63-year-old woman with left-sided ulcerative colitis (UC) diagnosed at the age of 23 was in clinical and endoscopic remission on 250 mg azathioprine (AZA) and sulfasalazine 4 g daily. AZA was discontinued after her diagnosis of metastatic melanoma, and she was started on immunotherapy with Ipilimumab and Nivolumab. After 4 cycles of treatment she presented with symptoms of diffuse abdominal cramping, bleeding per rectum and increased bowel frequency. Initial work up revealed CRP 2.5 mg/dL (normal: 0.5 mg/dL), and stool studies that were negative for any bacterial infection, including Clostridium difficile, or parasitic infection. Colonoscopy demonstrated moderate inflammation, Mayo Clinic Score 2 (MCS), extending continuously from the rectum proximally to 35 cm from the anal verge, with gradual transition to normal healthy mucosa in the proximal colon. Pathology showed cryptitis and crypt abscesses with focal ulceration in the recto-sigmoid colon. Initial trial of oral prednisone failed to achieve induction. Her immunotherapy was held and she was started on Vedolizumab therapy. She was successfully tapered off of steroids and achieved clinical and endoscopic remission after 7 months of maintenance therapy with Vedolizumab. Follow-up colonoscopy demonstrated mildly active pan-ulcerative colitis (MCS 1). Subsequently, she was able to resume treatment with Nivolumab monotherapy without any issues. The patient continues on Vedolizumab every 4 weeks as her maintenance therapy for UC. DISCUSSION: There have been a few reports documenting clinical outcomes of Vedolizumab therapy in patients with IMC. To our knowledge, there is no published data on the specific management of pre-existing IBD in patients starting immunotherapy. Our case is unique in that the patient had achieved clinical remission of her UC while on AZA, but required discontinuation of therapy after diagnosis of cancer. It is important to raise awareness among clinicians on the aftermath of discontinuing IBD therapy for patients who are anticipating immunotherapy. This special population requires a multidisciplinary approach and an integrated management plan in order to avoid potentially life-threatening immune-related adverse events and a flare from underlying IBD. Switching to therapies with a better safety profile and no systemic immunosuppression, like anti-integrins, might be a possible option both prior to and during immunotherapy. Whether this will decrease the incidence of future IMC in this population is yet to be supported with future research.